Factors associated with increased mortality in hospitalized COVID-19 patients. (December 2020) - Shah, Chirag; Grando, Donna J.; Rainess, Rebecca A.; Ayad, Lydia; Gobran, Emad; Benson, Payam; Neblett, Meika T.; Nookala, Vinod
Abstract: Background: The rapid spread of the coronavirus disease 2019 (COVID-19) epidemic has significantly impacted global health. So far, the evidence regarding the risk factors that predict the outcomes of COVID-19 patients is limited. In this study, we identified several risk factors that are associated with increased mortality in COVID-19 patients. Methods: We performed a retrospective review of electronic medical records of the patients admitted with an initial diagnosis of COVID-19. We extracted several patient variables (including demographics, lab results, and pre-existing conditions) and examined for their association with increased mortality. Results: Of the 487 people included in the study, 340 survived and 147 expired. Significant differences existed in demographics and underlying comorbidities between the two groups. A higher proportion of patients were age 65 and older (87.76% vs 53.24%, p < 0.001), and were predominantly male (63.27% vs 52.94%, p = 0.0351). Multivariate analysis showed five variables to be the predictors for mortality: age ≥65 [OR = 3.87, 95% CI (2.01, 7.46), p < 0.001], initial presentation with dyspnea [OR = 1.71, 95% CI (1.03, 2.82), p = 0.037], history of cardiomyopathy [OR = 3.33, 95% CI (1.07, 10.41), p < 0.038], positive initial chest imaging findings [OR = 2.24, CI (1.26, 3.97), p = 0.006], and acute kidney injury (AKI) [OR = 3.33 CI (2.10, 5.28), P < 0.001]. Conclusion: Identifying COVID-19 patients with these characteristics may help guide the management and improve mortality. Highlights: The evidence regarding the risk factors associated with mortality in COVID-19 patients is limited. Advanced age, an initial presentation with dyspnea, and positive chest imaging findings are associated with increased mortality. Past history of acute kidney injury and cardiomyopathy are associated with increased mortality. Early identification of the patients with an increased risk that require early medical intervention may reduce overall morbidity and mortality.